EVALUATION INFORMATION ON INCLUSIVE EDUCATION - Vitorino, Stephania Cottorello [UNESP]; Duarte Grego, Sonia Maria [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This work seeks to understand how has been articulated the proposal of inclusive education and evaluation within the school, but precisely with the instrument portfolio termed as instrument of formative assessment with students with intellectual disabilities of elementary school I in a public school from Sao Paulo state. The research of which originates from the present study is in progress. The proposed work consisted in carrying out a qualitative study of empirical nature, in line with the interpretative critical hermeneutics. In this approach the research involved two analysis procedures: document analysis and critical interpretative analysis of the productions of the students with intellectual disabilities in formative assessment through portfolios in the everyday life of the school. Among the material already studied about the assessment can verify that is relevant for the opportunity to discuss various aspects and ways of formative assessment as a tool that can facilitate and enrich the action of inclusive schools proposal of Municipal Public Network in the form of collaborative partnership, which can encourage the improvement of the teaching practice with action-reflection-action.
Keywords: Inclusive education; Formative assessment and intellectual disabilities